''I thought they should know... that daddy is not completely gone'': A Case Study of Sense-of-Presence Experiences in Bereavement and Family Meaning-Making. (March 2017) - Steffen, Edith; Coyle, Adrian
This study aimed to explore the experiences, responses, and conceptualizations of sense of presence experiences in bereavement in terms of family meaning-making. A case study framework was chosen, using group and individual interviews and ethnographically derived observations in a father-bereaved family in the south of England. Interview data were analyzed by applying both phenomenological and social constructionist perspectives to the same data set. It was observed that there was a division between the mother, who had derived much personal benefit from sense of presence experiences, and the children, who dismissed the experiences as incompatible with their own worldviews and how they made sense of their father's death.